Heart Rate Variability as a Biomarker of Chronic Stress in Healthy Men (2025)
ABSTRACT: This doctoral thesis delved into the relationship between allostatic load (AL) and heart rate variability (HRV) in healthy men, with a particular focus on HRV as a biomarker of chronic stress. Our research, which emphasizes a healthy population sample, significantly contributes to the field of preventive medicine. After establishing the theoretical framework, we conducted a scoping review to summarize the current evidence on the relationship between AL and HRV, confirming the gap in the topic. Subsequently, we conducted a cross-sectional study with healthy adult men from Medellín, Colombia. We developed an allostatic load index (ALI) and extracted HRV metrics from 24-hour Holter monitoring. Multiple linear regression models were used to evaluate the relationship between ALI and HRV. Additionally, we used magnetic resonance imaging to explore how ALI interacts with brain connectivity and structure in relation to HRV. Our study included 88 men aged 21-40, with 70% from middle socioeconomic backgrounds. We developed a new ALI using seven parameters (waist to height ratio -WHtR-, high density cholesterol -HDL-, glycosylated hemoglobin, HbA1C, c reactive protein -CRP-, systolic and diastolic blood pressure, and dehydroepiandrosterone sulfate -DHEAS-). The ALI was correlated with sympathovagal quotient -SQ- after adjusting for confounders (β = 0.093, p = 0.004, CI = 0.03-0.15). In the exploratory MLR analyses of the interaction between ALI-7, resting-state brain networks, and structures of the central autonomic network, several interactions had negative correlations with HRV. These findings suggest that the SQ is an indicator of AL, highlighting its potential as a biomarker for preventing, diagnosing, and managing chronic stress. Our exploratory analysis indicates that HRV reflects the interplay of central and peripheral physiological processes related to chronic stress. This finding underscores the need for validation in future research, which could further contribute to the field of preventive medicine.